The Effect of Basic Life Assistance (BHD) Education on the Knowledge Level of Long-Distance Runners in the RIOT Gorontalo Community - Ilham L. Ahmad; Ita Sulistiani; Ibrahim Suleman (Universitas Muhammadiyah Palu, 2026)
Sudden cardiac arrest is a serious health threat in long-distance running that requires rapid treatment through Basic Life Assistance or BHD to increase the chances of safety of the victim. However, runners' knowledge of the procedure is often not optimal, so structured education is needed. This study aims to analyze the influence of BHD education on the level of knowledge of long-distance runners in the RIOT Gorontalo community. This research method uses a pre-experimental one-group pretest-posttest design. The population of this study is Long Distance Runners in the RIOT Gorontalo Community, totaling 120 respondents. The sample was mixed with the purposive sampling technique totaling 55 respondents who were given interventions in the form of education using lecture methods and simulations measured through questionnaires. The data analysis of this study used the Wilcoxon Signed Ranks Test. The results showed that before the intervention, the majority of respondents had sufficient category knowledge as much as 56.4%, but after being given education, there was a significant increase where 52.7% of respondents reached the good category. Statistical results showed a p-value of less than 0.001 (<0.05) which proved the very significant influence of BHD education on improving runners' knowledge. These findings are expected to be the foundation for the running sports community in developing routine safety training programs to improve the preparedness of community members in dealing with cardiac emergencies on the running track.